(untitled) - Richards, Jack C. (New York, US, 2013)
Student's Book, Level 2 builds on the foundations established in Level 1 for accurate and fluent communication, extending grammatical, lexical, and functional skills. The Student's Book contains 16 teaching units, progress checks, additional Interchange activities, and a Grammar Plus section that provides additional grammar explanations and practice. Included is a Self-study DVD-ROM that provides the full class video and extra practice with vocabulary, grammar, speaking, listening, and reading.
Keywords: Ngôn ngữ tiếng Anh,English language,Ngôn ngữ tiếng Anh,English language